(untitled) (Journal of Economic Research & Business Administration, 2018)
The current stage in the development of the world tourism market shows that competition between tourist destinations regarding investments, information, transport and tourist flows, environmental, economic, social and cultural projects, ideas and, of course, specialists with value in the labor market is becoming more acute. Further, according to experts’ forecasts, interregional competition will intensify, and in the best position will be those of the tourist regions that not only possess the claimed regional resources, but also will be able to use them with benefit for their development. In the conditions of such interregional competition, the role of the formation of one’s own individuality, allowing the tourist destination to attract and increase resources for its development, increases. Thus, the relevance of the theme of creating a tourism brand is determined by a new stage in the development of society, accompanied by the growth of the influence of mass media and the formation of brand perception as a new intangible asset creating added value and a new competitive advantage. The creation of a tourist brand is, in a sense, also a requirement of time, determined by the growing strength of market relations in the context of globalization. The purpose of the article is to demonstrate the primary role of the construction of the country’s tourism brand in the development of the Kazakhstan tourist industry. The authors provide a multi-level system of marketing strategy for promoting the country’s tourism brand at the level of the country, region and product; suggest specific steps and mechanisms for its creation; give examples of foreign practice; outline the vision of the country’s tourism product line at the regional level and with a single link to the common brand. The construction of the country’s tourism brand and high-quality effective implementation of the marketing strategy for its promotion will increase the flow of foreign tourists and bring the industry to a more developed level.